(untitled) (Intent Research Scientific Journal, 2023)
This article covers the results of the construction and verification of data and devices on consumable freshwater extraction technology and economically efficient solar water chiller devices from marine and underground salt waters, which are unsuitable for consumption due to the sharp increase in the consumption water needs of the population of the growing world.